Ethylene Glycol Toxicity and Its Therapy Management: A Literature Review - Kurniawan, Robi; Hanifah, Suci (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Ethylene glycol (EG) is an antifreeze substance commonly used as an additive for syrup preparations. One of the detrimental effects caused by EG toxicity is acute renal failure (ARF) and death, assuming therapy and management are delayed. Presently, there are limited studies on toxicity of EG and therapy. Therefore, this study aimed to provide an overview of EG toxicity levels, clinical manifestations, arising reactions, and therapy management methods.Objectives: A narrative review design was employed with data collected from PubMed and Google Scholar. The strategy used keywords such as “ethylene glycol toxicity” and